Pembelajaran Qawaidul Imla’, Konsepsi, Problematika dan Solusinya - Moh. Anwar (Tafhim Al-'Ilmi, 2022)
AbstractWriting skill is one of the skills learned in learning Arabic in addition to the other three skills. By mastering writing skills, the competence of a student will be more complete. Writing skills in the context of learning Arabic include two aspects, namely writing skills related to the ability to write words and sentences correctly in accordance with Arabic writing rules, and writing skills related to the ability to express ideas in the form of essays. In the first aspect, writing skills are framed in a discipline known as Qawaidul Imla '. In this science, the rules or rules for writing Arabic are studied correctly in accordance with what has been agreed upon by the scholars in their field. So this paper tries to explore the nature of learning qawaidul imla 'at all levels of education in general. The author tries to emphasize the conception of qawaidul imla' learning, the purpose of qawaidul imla', qawaidul imla' material, various problems and problems faced by students in learning imla' and several offers of solutions. Keywords: Qawaidul Imla ', Conception, Problematic, Solution